2020
DOI: 10.1002/ldr.3524
|View full text |Cite
|
Sign up to set email alerts
|

Amendments with humified compost effectively sequester organic carbon in agricultural soils

Abstract: Preventing degradation of soil quality and productivity entails development of sustainable practices to enhance soil organic matter. We followed soil organic carbon (OC) accumulation during 3 years long‐field experiments in two different Italian soils under conventional tillage (TRA), reduced tillage (MIN), green manure (GM) and two rates (low, CMPL, and, high, CMPH) of mature compost amendments. Despite soil textures differences, CMP additions enhanced in both field sites OC accumulation in either bulk soils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…At the same time, the enzymes related to organic carbon mineralization, i.e., K05349 (beta-glucosidase [EC: 3.2.1.21]) and K15371 (glutamate dehydrogenase (GDH2) [EC: 1.4.1.2]), decreased. These results showed that the soil management under rainfed conditions proposed in this study (i.e., compost amendment and incorporation of weed biomass in an olive grove) affected some pathways of soil metabolism and environmental information processing in a manner comparable to that evidenced by other authors and for conservation management [54,55], promoting the humification of both exogenous and natural organic carbon [56]. Finally, we did not find significant differences in the global metabolic pathways related to the P cycle (K01113_K01077_alkaline phosphatase).…”
Section: Bacterial Community Functional Potentialsupporting
confidence: 77%
“…At the same time, the enzymes related to organic carbon mineralization, i.e., K05349 (beta-glucosidase [EC: 3.2.1.21]) and K15371 (glutamate dehydrogenase (GDH2) [EC: 1.4.1.2]), decreased. These results showed that the soil management under rainfed conditions proposed in this study (i.e., compost amendment and incorporation of weed biomass in an olive grove) affected some pathways of soil metabolism and environmental information processing in a manner comparable to that evidenced by other authors and for conservation management [54,55], promoting the humification of both exogenous and natural organic carbon [56]. Finally, we did not find significant differences in the global metabolic pathways related to the P cycle (K01113_K01077_alkaline phosphatase).…”
Section: Bacterial Community Functional Potentialsupporting
confidence: 77%
“…37 The substitution of compost at the latter stage of the experiment may have added more stable forms of C. The addition of humified compost is an effective strategy to store C in agricultural soils. 38 Even though the biochemical recalcitrance of the compost is unknown, 7 the added compost (after 2000) may have played a significant role in increasing SOC. Previous research from the studied agroecosystem, indicated that the organic additions (1992−2014) resulted in an increase of 65% and 228% in SOC in tilled and no-till soils (0−5 cm depth), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Humified mature composts were observed to promote the stability of SOM in agricultural soils and significantly increased the content of non-polar alkyl and aromatic moieties after 3 years of application (Spaccini and Piccolo, 2020). Spaccini et al (2019) reported that the biochemical stability of ligno-cellulose residues from biorefinery wastes was similar to that found for the persistent fraction of SOM.…”
mentioning
confidence: 77%
“…For example, organic amendments rich in alkyl and N‐alkyl groups improved soil organic C (SOC) content and accelerated macroaggregation in soils (Yu et al., 2015). Humified mature composts were observed to promote the stability of SOM in agricultural soils and significantly increased the content of nonpolar alkyl and aromatic moieties after 3 yr of application (Spaccini & Piccolo, 2020). Spaccini et al.…”
Section: Introductionmentioning
confidence: 99%